(untitled) (Scientia Agricola, 2001)
The tomato pinworm Tuta absoluta (Meyrick) is one of the main tomato pests in Brazil. With the objective of obtaining an efficient and not pollutant method of control, the activity of aqueous extracts of Trichilia pallida Swartz leaves and twigs on this pest was studied associated to the tomato cultivars Santa Clara and IPA-5. The development of the insect was observed on leaves of each cultivar, previously treated with extracts at 1% of concentration. Length and viability of larval and pupal stages and pupal weight were evaluated. The larval period of the insect was more prolonged on 'IPA-5' and, when associated with leaf and twig extracts, reduced pupal viability. Leaf and twig extracts also prolonged the larval stage in 'Santa Clara'. The leaf extract affected more negatively the insect development than the twig extract, reducing larval viability on both cultivars.